Motivations of Fur Trappers in Interior Alaska. Issue 6 (1st November 2016) - Dorendorf, Ross R.; Fix, Peter J.; Prugh, Laura R.
ABSTRACT: Understanding how and why trapping effort varies among fur trappers is necessary to accurately interpret trends in fur harvest for wildlife management. We mailed questionnaires to 1, 760 fur trappers in interior Alaska to characterize motivations for trapping and primary factors affecting trapping effort. A cluster analysis revealed four groups with distinct motivations for trapping: wildlife management (17% of trappers), recreation (39%), subsistence (18%), and solitude (26%) trappers. Perceived furbearer abundance had the greatest effect on trapping effort, while access to land and human conflicts were the most important social issues to trappers. Economic gain was the least important motivation for trapping among respondents. Because trapping effort mirrored furbearer abundance, harvest-based abundance indices may amplify true changes in population sizes. Our findings also suggested that managers seeking to maintain or increase satisfaction among trappers should focus on reducing human conflicts and maximizing the non-monetary benefits of trapping.